Multidrug resistant Salmonella sp isolated from chicken - Victor, Atere (International Journal of Biological Research, 2016)
Antibiotic resistance has been a major problem in combatting Salmonella in poultry, this research was designed to determine the antibiotic resistance level of Salmonella isolated from freshly dead chicken. A total of 107 freshly dead chicken were collected from 23 different farms, birds were necropsied, liver and trachea were collected, Salmonella were recovered from the samples using peptone water, Rappaport-Vassiliadis R10 Broth and Salmonella-Shigella agar. Pure culture were identified using cultural, morphological and biochemical characteristics. The pure isolates were subjected to antibiotic test using disc diffusion method. Sixteen isolates of Salmonella were recovered, 3 of which were from the trachea while 13 were recovered from the liver. All of the Salmonella isolates were resistant to Amoxicillin 100% while Nitrofuratoin was least resisted with only 37.5% of the Salmonella isolates showing resistance. The antibiotic resistant pattern often observed in this study were AMP, AUG, TLY with 75% (12); AMP, AUG, TLY, CPR, ENR, 50% (8); while 6.3% (1) was resistant to all of the antibiotics tested. This result showed that there is an emergence of multi-resistance Salmonella in poultry, therefore it is important to carry out sensitivity test before administration of antibiotics in order to control poultry salmonellosis.